Direct observation of structure-function relationship in a nucleic acid-processing enzyme - Comstock, Matthew J.; Whitley, Kevin D.; Jia, Haifeng; Sokoloski, Joshua; Lohman, Timothy M.; Ha, Taekjip; Chemla, Yann R. (Science (American Association for the Advancement of Science), 2015)
The relationship between protein three-dimensional structure and function is essential for mechanism determination. Unfortunately, most techniques do not provide a direct measurement of this relationship. Structural data are typically limited to static pictures, and function must be inferred. Conversely, functional assays usually provide little information on structural conformation. We developed a single-molecule technique combining optical tweezers and fluorescence microscopy that allows for both measurements simultaneously. Here we present measurements of UvrD, a DNA repair helicase, that directly and unambiguously reveal the connection between its structure and function. Our data reveal that UvrD exhibits two distinct types of unwinding activity regulated by its stoichiometry. Furthermore, two UvrD conformational states, termed "closed" and "open," correlate with movement toward or away from the DNA fork.